Navigating NHS commissioning for digital mental health: a perspective on learning through collaboration - Hall, Charlotte L.; Prentice, Kelly-Marie; Hastings, Olivia; Babbage, Camilla M.; Hall, Sophie S.; Bolton, Sarah J.; Bouttell, Janet; Gibbons, Jonathan; Patel, Julian; Watts, Michael; Davies, E. Bethan; Groom, Madeleine J.; et al. (Frontiers in Health Services, 2025)
Digital mental health interventions (DMHIs) offer promising solutions to address unmet mental health needs among children and young people, yet how to get DMHIs commissioned into the NHS can seem mystifying for innovators. This perspective paper draws on insights from a collaborative commissioning event focused on the Online Remote Behavioural Intervention for Tics (ORBIT) intervention, a digital behavioural therapy for young people with tic disorders, to explore the barriers and enablers to commissioning DMHIs in England. Key challenges identified include unclear commissioning pathways, limited clinical expertise, integration hurdles, and short-term funding models. Enablers included clinical advocacy, robust research evidence, and alignment with national frameworks. These insights highlight the importance of early collaboration between academics, developers, and policymakers in the product development cycle seeking to bridge the gap between innovation and implementation in digital mental health care.